The halalan thayyiban supply chain in handling blood products of slaughtering cattle, chicken, and pig for feeding and handling al-jallalah 1 (cattle, chicken, and catfish) - Maryuliano, Ilham; Andarwulan, Nuri (Halal Studies and Society, 2024)
Blood from the slaughter of cattle and chicken, is an economically valuable waste that can not be disposed into the environment. Its application in animal feed requires careful consideration of the composition and potential impact. The Indonesian Ulema Council issued a Fatwa regarding the Law on Livestock Animals Fed with Unclean Items. From a Sharia perspective, the feed composition is crucial, since it needs to be free from unclean ingredients to prevent animals from becoming classified as Al-Jallalah (Livestock Animals Fed with Unclean Items). To ensure compliance with the religious guidelines, it is necessary to implement a quarantine (Al-Istibra) or purification period (Istihalah). Therefore, this study aimed to analyze the halalan thayyiban supply chain in the management of blood from slaughtering ruminants (cattle), poultry (chicken), and pig for feed. Implementation of good practices in managing blood from slaughterhouses was assessed. The suitability of feed labels, including the presence of prohibited ingredients, adherence to good practices, and the application of Al-Istibra or Istihalah in cattle and chicken farms, as well as catfish farming units, was evaluated through questionnaire interviews and conformity scores. The results showed that 2 out of 7 (seven) objects received lower scores due to the limited effectiveness of the Waste Water Treatment Plants (WWTPs) and unclear regulations regarding the use of blood. Based on the suitability value of the feed label, 1 (one) out of 8 (eight) objects received a lower score for failing to meet technical requirements. The feed was contaminated, and there were no operational procedures for implementing Al-Istibra or Istihalah.